Slashing IC Power and Democratizing IC Access for the Digital Age - Kuroda, Tadahiro (IPSJ Transactions on System and LSI Design Methodology, 2024)
The continuous growth of the semiconductor industry, driven by the use of AI to fuse the physical with virtual space, requires drastic improvement in IC power efficiency, memory capacity, and memory bandwidth. This paper describes two solutions to slash IC power using 3D integration and specialized chips. In addition, it proposes a novel sliced bread memory stacking scheme that enables more than a 10-fold increase in the number of memory chips and hence capacity per stack, as well as memory bandwidth. Furthermore, it elaborates on an agile development platform that enables designing chips like writing software and prototyping chips in days. The ease of use of the platform and its 10-fold reduction of development time and costs are expected to democratize access to specialized chips to accelerate innovation by increasing the number of developers. It will also accelerate the transition of society to the digital age. Finally, the author will discuss the need for the global IC industry to move away from its reliance on competition to co-existence and co-evolution to sustain its growth.